Pengaruh Penerapan Manajemen Kelas Dan Literasi IPS Terhadap Hasil Belajar IPS Di SDN 60 Moncongloe Lappara Kec. Moncongloe Kab. Maros - Ramli Ramli; Muh. Yunus; Husain. As (Departement of Mathematics Education, 2023)
The Effect of the Application of Classroom Management and Social Studies Literacy on Student Learning Outcomes at SDN 60 Moncongloe Lappara, Moncongloe District, Maros Regency. Guided by Muh. Yunus and Husain AS.This study aims to 1) to determine the effect of classroom management on social studies learning outcomes of SDN 60 Moncongloe Lappara Kec. Moncongloe Kab. Maros. 2) To determine the effect of IPS literacy on social studies learning outcomes of SDN 60 Moncongloe Lappara Kec. Moncongloe Kab. Maros. And 3) To determine the effect of classroom management and social studies literacy which is significant on social studies learning outcomes of SDN 60 Moncongloe Lappara Kec. Moncongloe Kab. Maros. This research was conducted at SDN 60 Moncongloe Lappara Kec. Moncongloe Kab. Maros from December to May 2023. This research uses a quantitative research type with an ex post facto approach. Data collection techniques with questionnaires. The population in this study were high grade students, namely grades 4, 5 and 6 of SDN 60 Moncongloe Lappara, Moncongloe District, Maros district, with a total of 326 students. The sampling technique used was random sampling, the sample used was 82 students. The results showed that the results of the partial test showed that 1) class management had a significant effect on social studies learning outcomes of students at SDN 60 Lappara Moncongloe Kec. Moncongloe Kab. Maros. 2) The results of the partial test show that Literacy has a significant effect on social studies learning outcomes of students at SDN 60 Lappara Moncongloe Kec. Moncongloe Kab. Maros. And 3) The results of the simultaneous test show that class management and literacy jointly influence the social studies learning outcomes of students at SDN 60 Lappara Moncongloe Kec. Moncongloe Kab. Maros. Classroom Management and Literacy Variables Affect Student Learning Outcomes by 70.4% and the remaining 29.6% are influenced by other factors in this study.